Determination of some properties of used cooking oil using AAS, bomb calorimeter and GC-MS techniques - Khalid, Khalisanni; Khalid, Khalizani; Othman, Maizatulnisa; Ku Hamid, Ku Halim; Chowdury, Zaira Zaman (2011)
Most of the used cooking oil from households and catering premises in Malaysia will eventually ends up in wastewaters. It will be discharged to the surface of waters because no alternative steps were taken to overcome the waste from used cooking oil. As a component of wastewater, oil is classified together with fats and waxes as grease. This trend results in the generation of a vast waste stream that needs to be properly managed to avoid environmental damage. Thus, the information regarding on the waste cooking oil properties is needed to contribute knowledge for future research where the waste may reformed to value added product. Preliminary analysis of used cooking oil properties via GCMS using capillary column shows n-Hexadecanoic acid and Oleic acid as the major compounds present in the used frying oil. The analysis for determination of volatile and moisture content with 3 replicates show an average of 0.02% moisture and volatile content, which the experimental procedure was based on MPOB Test Methods.